The Role of Medan City Market PUD in Market Management in Medan - Martua Raya Hasibuan; Maryam Batubara (Penerbit Jurnal Indonesia, 2022)
PUD is a legal entity in which there are business activities based on regulations made by the local area. PUD (Regional Public Company) is one of the BUMDs where the capital is wholly owned by a region. This research is useful for reviewing the role of Medan market PUD in market management in Medan. The method used in this research is qualitative method. The results of this study indicate that the role of PUD in market management in Medan is running well. However, there are several things that need to be improved, such as market management.